Serratus Plane Block Is Effective for Pain Control in Patients With Blunt Chest Trauma: A Case Series. Issue 2 (31st October 2019) - Martinez, Thibault; Belveyre, Thibaut; Lopez, Alexandre; Dunyach, Chloe; Bouzit, Zina; Dubreuil, Guillaume; Zetlaoui, Paul; Duranteau, Jacques
Abstract: Background: Rib fractures occur frequently following blunt chest trauma and induce morbidity and mortality. Analgesia is a cornerstone for their management, and regional analgesia is one of the tools available to reach this objective. Epidural and paravertebral blocks are the classical techniques used, but the serratus plane block (SPB) has recently been described as an effective technique for thoracic analgesia. Methods: This case series reported and analyzed 10 consecutive cases of SPB for blunt chest trauma analgesia in a level 1 trauma center from May to October 2018. SPB was performed with either a single shot of local anesthetic or a catheter infusion. Results: Ten patients were treated with 3 single shots and 7 catheter infusions (median length 3 days [interquartile range (IQR) 2.5 to 3.5]). The Median Injury Severity Score was 16 (IQR 16 to 23), and the number of broken ribs ranged from 3 to 22. Daily equivalent oral morphine consumption was significantly decreased after SPB from 108 mg (IQR 67 to 120) to 19 mg (IQR 0 to 58) ( P = 0.015). The Numeric Pain Rating Scale (NPRS) score during cough was significantly decreased from 7.3 (IQR 5.3 to 8.8) to 4 (IQR 3.6 to 4.6) ( P = 0.03). The NPRS score at rest remained unchanged. One complication occurred, due to a catheter section. Conclusions: The SPB technique (with or without catheter insertion) in 10 patients who had blunt chest trauma with rib fractures is effective for cough pain control, with a significant decrease in morphine consumption.